2013
DOI: 10.1021/jo401316a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic and Chiroptical Studies on the Desulfurization of Epidithiodioxopiperazines Reveal Universal Retention of Configuration at the Bridgehead Carbon Atoms

Abstract: The stereochemistry of the desulfurization products of chiral natural and synthetic 3,6-epidithiodiketopiperazines (ETPs) is specified inconsistently in the literature. Qualitative mechanisms have been put forward to explain apparently divergent stereochemical pathways, but the quantitative feasibility of such mechanistic pathways has not been assessed. We report a computational study revealing that desulfurization of ETPs should occur universally with retention of configuration. While the majority of stereoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…Amongst others, these include sirodesmin A, sporidesmin A, chaetocin, aranotin, and chetomin [13]. Studies on the biosynthetic mechanism of ETPs, particularly gliotoxin, are also serving to inspire new synthetic chemistry approaches for ETP synthesis and desulfurization, which are somewhat beyond the scope of the present review [13,14].…”
Section: Contextualizing and Rethinking Gliotoxinmentioning
confidence: 97%
See 1 more Smart Citation
“…Amongst others, these include sirodesmin A, sporidesmin A, chaetocin, aranotin, and chetomin [13]. Studies on the biosynthetic mechanism of ETPs, particularly gliotoxin, are also serving to inspire new synthetic chemistry approaches for ETP synthesis and desulfurization, which are somewhat beyond the scope of the present review [13,14].…”
Section: Contextualizing and Rethinking Gliotoxinmentioning
confidence: 97%
“…Amongst others, these include sirodesmin A, sporidesmin A, chaetocin, aranotin, and chetomin [13]. Studies on the biosynthetic mechanism of ETPs, particularly gliotoxin, are also serving to inspire new synthetic chemistry approaches for ETP synthesis and desulfurization, which are somewhat beyond the scope of the present review [13,14].In addition to studying how gliotoxin contributes to organismal virulence, it has also been deployed to explore and reveal novel biochemistry within both fungal and animal cells [15,16]. Thus, we contend that it is the ability of gliotoxin to interfere with so many cellular processes that makes it such a useful tool to access the many important, although occluded, systems interactions within fungi.…”
mentioning
confidence: 97%
“…Compound 189 was found to adopt a bracelet-type structure in inert solvents, while a propeller-type structure was suggested in polar solvents. 194 Furthermore, a combination of chiroptical spectroscopic methods was successfully applied to two new dimeric epipolythiodiketopiperazines, preussiadins A (191) and B (192), obtained from the mycelia of a Preussia typharum isolate. It was found that the most populated conformer does not exhibit C 3 symmetry, and is different from that present in the crystal and the NMR-derived strucuture.…”
Section: Peptides and Carbohydratesmentioning
confidence: 99%
“…The errors in the literature ACs can be traced back to varying sources, which are detailed in the footnotes to Table . For detailed discussions on individual cases, the reader is encouraged to refer to the cited references …”
Section: Errors Uncovered In the Literature Acs During Modern Chiroptmentioning
confidence: 99%